Correction to: Paradigm shift in Traditional Mongolian medicine in the 18th century Vol. 63 No 02 (246) 2023 in Proceedings of the Mongolian Academy of Sciences, 63(02), 19–24. - Damiran, Enkhamgalan; Khailan, Ulaan-Od; Dashjamts, Shagdarsuren; Battogtokh, Gerelmaa; Sharavyn, Bold (Proceedings of the Mongolian Academy of Sciences, 2025)
In the original publication one of the Enkhamgalan Damiran’s proper affiliation requested to change. The new affiliation for Enkhamgalan Damiran changed as follows. “Mongolian Academy of Medical Sciences, Mongolian Academy of Sciences, Ulaanbaatar, Mongolia” to the 2th affiliation and “School of Governance and Management, National Academy of Governance, Ulaanbaatar, Mongolia to the 1th affiliation” The authors state that the scientific conclusions are unaffected. This correction was approved by the Co-authors. The original article can be found online at https://doi.org/10.5564/pmas.v63i02.1417